Analysis of Criminal Convictions of Perpetrators of Unpleasant Acts - Cipta Hatimbulan T; Maya Jannah; Abdul Hakim (International Journal Labs, 2023)
This study aims to find out and analyze the criminal punishment of perpetrators of unpleasant acts. As well as knowing and analyzing the analysis of criminal convictions against perpetrators of unpleasant acts (decision study number: 386 / pid.b / 2013 / pn.rhl). This research is a type of normative research so it can be known that this article can become a rubber article if there is no measure of the extent to which the insult judgment can occur. So the measure is very subjective and based only on the assessment of victims, investigators, and public prosecutors alone.